Students’ Work Skill In Making Bed On Industrial Practices Implementation In Hotel - Sumiati, Nelis; Rohaeni, Neni; Jubaedah, Yoyoh (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2018)
This research is motivated by the importance of students' ability in making bed on the Industrial Practice (IP) implementation that has not complied with hotel’s Operational Standard. The Aim of this study is to obtain students' work skills in practicing stripping bed, and making bed. The research method used in this research is descriptive method, and use instrument in the form of performance criterion by using scale four. Sampling technique in this research used purposive sampling. The research result of students’ work skill in making bed based on hotel’s Operational standard includes two stages implemented by students consist of preparation stage or stripping bed, and the process of making bed. The students’ skill in preparation stage or stripping bed is more shown in the preparing practical equipment aspect that is preparing linens for making bed. The students’ skill at the implementation stage of making bed is more indicated in process of making bed practice implementation. Most of the students gain very capable results according to hotel’s Operational standard, meanwhile there are still some students gain capable result and less capable result in making bed in Industrial Practice implamantation in hotel. The result of this research is expected to be used as input for Family Walfare Study Program of House Keeping concentration students who will conduct Industrial Practice in the future to be able to maintain the ability in the of making bed practice according to hotel’s operational standard.